2020
DOI: 10.1590/1809-4430-eng.agric.v40n4p495-502/2020
|View full text |Cite
|
Sign up to set email alerts
|

Design of Electronic Control Governor for a Single Cylinder Gasoline Engine Based on an Intelligent Sensing Algorithm

Abstract: At present, most large machinery and vehicle engines are electronically controlled but their electronic control systems are too expensive to be popularised and applied in small gasoline engines with relatively low prices. Therefore, small gasoline engines still use mechanical speed regulators. Mechanical speed regulators not only have the defects of inertia lag, friction resistance, inherent speed regulation and the like, but also have the disadvantage that dynamic performance and steady performance cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Fourth, the y-axis motor continues to work, the photoelectric switch reaches the first empty position, the y-axis motor stops working, the unlocking column crosses the sorting device, waiting for feeding, the sorting slot returns to the initial state, keeps the fixed suction head, and the impeller motor returns to work to feed the sorting slot (Pei et al, 2019). Fifth, after the sorting slot is filled with suction heads again, the impeller motor stops working; then the above steps are repeated, and the photoelectric switch successively reaches the second unlocking position, the second vacant position, the ninth unlocking position and the ninth vacant position; the second, third and ninth rows of suction head storage holes are filled one by one, and finally the filling of the suction head storage box is completed (Sun et al, 2020;Xu et al, 2018).…”
Section: Software Design Of Automatic Packing Equipment For Pipette S...mentioning
confidence: 99%
“…Fourth, the y-axis motor continues to work, the photoelectric switch reaches the first empty position, the y-axis motor stops working, the unlocking column crosses the sorting device, waiting for feeding, the sorting slot returns to the initial state, keeps the fixed suction head, and the impeller motor returns to work to feed the sorting slot (Pei et al, 2019). Fifth, after the sorting slot is filled with suction heads again, the impeller motor stops working; then the above steps are repeated, and the photoelectric switch successively reaches the second unlocking position, the second vacant position, the ninth unlocking position and the ninth vacant position; the second, third and ninth rows of suction head storage holes are filled one by one, and finally the filling of the suction head storage box is completed (Sun et al, 2020;Xu et al, 2018).…”
Section: Software Design Of Automatic Packing Equipment For Pipette S...mentioning
confidence: 99%
“…The study results showed that optimal fuel pressure can be obtained even at low engine speeds. Sun et al (2020) also improved the performance of diesel motors through fuel injection by applying electronic governor control with an intelligent sensing algorithm, resulting in increased power, reduced fuel consumption, and enhanced operational stability. Kapilan et al (2009) reported the same trend of increasing fuel injection pressure to improve engine performance.…”
Section: Introductionmentioning
confidence: 99%